PENERAPAN TRI HITA KARANA PADA MANAJEMEN SATRIA AGROWISATA DI KECAMATAN TAMPAKSIRING, KABUPATEN GIANYAR - Desak Putu Padmidewi; Wayan - Windia; I Made Sudarma (Universitas Udayana, 2019)
ABSTRACT Tri Hita Karana has becomes the foundation of development in the Province of Bali, its reflected in the vision of the development in the Province of Bali in 2006-2026